Impingement factors affecting the human development index among the river communities of the Tembeling, Pahang and Muar Rivers - Abu Samah, Asnarulkhadi; Mazuki, Raidah; Md. Yassin, Sulaiman; Abu Samah, Bahaman (Universiti Putra Malaysia Press, 2018)
There are few studies on the Human Development Index (HDI) with regard to the community and very little is known about the community development index and the factors that impinge on it. This study seeks to fill this gap, and makes the examination of the factors that impinge on the human development index among river communities its main focus. This is a quantitative study and the measurement of the HDI is based mainly on an established online instrument. A total of 240 respondents, who were the villagers of four selected villages, make up the respondents of the study. Analysis confirms that factors such as gender, race, level of education, area and job category lead to significant differences of the HDI, while further analysis concludes that factors such as income, period of stay, distance to the nearest city and size of household have a significant relationship with HDI. The discussion will help the concerned parties to construct a workable strategy to further improve the HDI of the locals, particularly those who are settled near the Tembeling, Pahang and Muar Rivers.